2013
DOI: 10.1371/journal.pone.0076795
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Five Serum Protein Markers for Detection of Ovarian Cancer by Antibody Arrays

Abstract: BackgroundProtein and antibody arrays have emerged as a promising technology to study protein expression and protein function in a high-throughput manner. These arrays also represent a new opportunity to profile protein expression levels in cancer patients’ samples and to identify useful biosignatures for clinical diagnosis, disease classification, prediction, drug development and patient care. We applied antibody arrays to discover a panel of proteins which may serve as biomarkers to distinguish between patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…A study performed by Lane et al showed that OPG acts as a survival factor by protecting TRAIL-induced apoptosis of ovarian cancer cells (68). These reports indicate the potential role of OPG in both development and progression of ovarian cancer, and the study by Jiang et al suggests that a set of five serum markers, including OPG can be used for the detection of ovarian cancer (69). Our previous results of autoantibody profiling in ovarian cancer (8) and the current profiling of plasma samples from patients with breast cancer demonstrate elevated levels of OPG autoantibodies in the cancer groups.…”
Section: Discussionmentioning
confidence: 98%
“…A study performed by Lane et al showed that OPG acts as a survival factor by protecting TRAIL-induced apoptosis of ovarian cancer cells (68). These reports indicate the potential role of OPG in both development and progression of ovarian cancer, and the study by Jiang et al suggests that a set of five serum markers, including OPG can be used for the detection of ovarian cancer (69). Our previous results of autoantibody profiling in ovarian cancer (8) and the current profiling of plasma samples from patients with breast cancer demonstrate elevated levels of OPG autoantibodies in the cancer groups.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Meltzer et al examined 500 proteins via protein array in serum samples collected from rectal cancer, and found the expression of OPG was increased which was correlated with the survival of rectal cancer patients after chemotherapy [20]. Jiang et al analyzed 174 serum proteins of ovarian cancer using protein array screening, and discovered a significant difference of five proteins: MSP-alpha, TIMP-4, PDGF-R alpha, OPG and CA125, which might be regarded as diagnostic biomarkers for ovarian cancer [21]. We, for the first time, compared 507 serum proteins in PCOS patients and healthy controls with protein array, and identified 76 differentially expressed proteins, including 40 increased proteins and 36 decreased proteins, and 47 kinds of proteins were newly reported.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several ovarian cancer screening studies have established that acombinatorial biomarker strategy is more reliable, sensitive and specific than using a single protein biomarker [76]. A recent study identified a 5-marker panel for early detection of ovarian cancer that includes five serum biomarkers, namely macrophage-stimulating protein alpha, tissue inhibitor of metalloproteinases-4, platelet-derived growth factor receptor alpha (PDGF-R alpha), osteoprotegerin, and CA-125 [77]. Preliminary insights that we obtained using ProteINSIDE, a novel web service [78], suggest that among the genes highly expressed in SKOV-3 cells there are some that encode for secreted proteins like CGB5 [79], CGB8 [79], FOLR1 [28], SPP1 [80], IGFBP3 [81], NFASC [82] emphasizing that our study may indeed provide a solid basis for the identification of new biomarkers.…”
Section: Discussionmentioning
confidence: 99%